Consumer focused education on paracetamol side effects, inadequate outcomes and weaning for individuals with low back pain: protocol for a feasibility study - Patterson, Thomas; Turner, Justin Turner; Gnjidic, Danijela; Mintzes, Barbara; Baysari, Melissa; Bennett, Carol; Bywaters, Lisa; Clavisi, Ornella; Ferreira, Manuela; Beckenkamp, Paula; Ferreira, Paulo (International Journal of Clinical Trials, 2021)
Background: Prescription and over the counter medications, such as paracetamol, account for a significant proportion of the direct and indirect costs in managing low back pain (LBP). Existing research has not only questioned the efficacy of paracetamol use for musculoskeletal conditions such as LBP, but also its safety. No previous study has investigated the feasibility of a pharmacological education tool for individuals using paracetamol to manage their LBP. The aims of this study are to investigate: (1) the acceptability and experience of participants with the pharmacological education tool, (2) feasibility of recruitment, data collection and outcome measure completion, and (3) participant’s willingness to participate in a randomised control trial. Methods: This will be a single group repeated measures study design recruiting individuals from community organisations. Included participants will be over 18 years, experiencing acute, chronic or recurrent episodes of LBP and self-report consumption of paracetamol for pain relief weekly for at least one month. This study will be open for recruitment from June 2021 to August 2021. Conclusions: Our findings will inform the feasibility of conducting a larger randomised controlled trial. This study will be judged as feasible to proceed to a full trial based if, 1) recruitment sources are each able to enrol at least 20 participants into the study within three months of initial advertisement, 2) the majority of participants find the study and intervention experience as acceptable, and 3) there is less than 20% of missing data for the primary outcomes, and a minimum of 85% follow-up rate for enrolled participants.